The effectiveness of virtual passport, an app-based intervention, for dementia care - Hong, Qian-Xi; Wang, Wen-Fu; Yang, Yuan-Han; Tung, Yu-Chun; Dai, Hong-Jie; Hsu, Wen-Chuin; Huang, Ling-Chun; Jhang, Kai-Ming (Frontiers in Psychiatry, 2024)
This study aimed to confirm the effectiveness of the virtual passport for dementia care.The virtual passport is an application (app) tool connecting healthcare professionals, dementia care sites, and people living with dementia (PLWD) and their family caregivers. This tool assists case managers in hospitals by providing individualized care plans and health education to PLWD and their caregivers. The dementia quality indicator achievement rates, care needs investigation and fulfillment, severity of behavioral and psychological symptoms of dementia (BPSD), and changes in caregiver burden and depression are measured at the initial interview and 6 and 12 months after the intervention.We enrolled 57 and 54 patients and their caregivers in the virtual passport and routine care groups, respectively. Compared to the control group, six quality indicators in the passport group showed significantly higher achievement at 6 months after using the virtual passport. Case managers addressed more care needs at 6 months (1.37 vs 0, p < 0.001) and 12 months (1.32 vs 0, p < 0.001). Improvement in severity of neuropsychiatric symptoms (neuropsychiatric inventory (NPI) irritability/lability difference: -0.58 vs 0.22, p = 0.044; NPI agitation/aggression difference =-0.78 vs 0.00, p = 0.042) were also observed. No obvious influence was found in caregiver burden and depression after using the virtual passport.The virtual passport is an effective information technology tool in improving the quality of dementia care, assisting case management in identifying more care needs, and reducing the severity of BPSD.